Proceso atención de enfermería en neonato con complicaciones severes por parto distosico. - Quinatoa Patín, Mayra Lissbeth (2022)
Home deliveries or home deliveries are a common practice in rural areas of the country where access to health care is difficult, this empirical practice increases the risks of complications or maternal/infant death when assisted by a midwife without the due preparation. In the following case study, it is focused on a 5-hour-old newborn product of a home delivery, clubfoot is evident, the parents refer hypoactivity at the time of birth with crying after the minute of life, on the DOWNES scale 4/ 14 (moderate), body temperature below normal lameness (hypothermia), umbilical cord cut with household scissors, respiratory distress and neonatal sepsis determined. The nursing care process is elaborated using the Nanda, Nic and Noc taxonomy, to identify the dysfunctional patterns that are compromising the patient's health status, and thus meet the objectives proposed in this case study.